Medicalization and Cholera in Cordoba in the Late 19th Century. The Epidemics of 1867-68 and 1886-87 (2016)
After the first half of the 19th century elapsed, a new disease began to ravage the Argentine population, generating panic and measures taken by the State in order to fight it. Cholera punished Argentina three times in that half of century: 1867-68, 1886-87 and 1894-1895. It had an important impact in cities where, in turn, a growing modernization process was taking place. It was also the time when the medical elite began a slow but unavoidable legitimation and clambered in the State a candidate to become health safeguards. This article aims to analyze the strategies, practices and conflicts of the different stakeholders who participated in the first two cholera outbreaks that occurred in the city of Cordoba. These epidemics take on significant value because they are an indicator of the degree of insertion of the medical elite in the State and the strategies chosen by medicine and other social stakeholders to fight them. Thus, we believe that the establishment of certain institutions such as the Provincial Hygiene Council and the Local Public Health Service determined the rise of the medical elite at certain levels of the State; from those places they could legitimize with the development of fighting strategies.